Description of visceral, lymphatic and central nervous system lesions in dogs infected with Leishmania spp - Mendonça, Cinthian C.; Costa, Bruno M. P.; Brandão, Katharine M.; Maruo, Viviane M.; Maiorka, Paulo C.; Machado, Gisele F. [UNESP]; Cordova, Clarissa A. M.; Moron, Sandro S.; Sousa, Luciano F.; Hosomi, Fernando Y. M.; Graça, Dominguita L.; Ramos, Adriano T. (My University, 2013)
Leishmaniases are a group of chronic systemic infectious diseases caused by intracellular protozoa of the genus Leishmania. In the present study the authors aimed to investigate Leishmania spp-induced lesions mainly to detect the presence of the parasite within the CNS and lymph nodes in dogs from the Araguaina region, Tocantins State, Northern Brazil. Descriptive statistical analysis of variance and correlation were conducted, indicating that gross signs and visceral lesions do not correlate positively. Therefore we conclude that the diagnosis cannot be based on macroscopic signs alone presented by the infected dogs.
Keywords: Central nervous system; Dogs; Leshmania spp